Undergraduate Students’ Learning of Linear Algebra Through Mathematical Modelling Routes - Ramírez Montes, Guillermo Enrique (2021)
Mathematical modelling has acquired relevance at all educational levels in the last decades since integrating this activity in instruction provides significant contexts for improving students’ learning, including in linear algebra courses that have a notable presence in many undergraduate courses from different fields, including engineering and sciences. This paper reports a study aiming to characterize the distinct modelling routes performed by Costa Rican undergraduate students when solving a mathematical modelling task involving the concept of system of linear equations (SLE). In analysing those modelling routes, it was possible to identify their learning of linear algebra concepts and their modelling competencies as well as the associated difficulties that students faced. Data collection included participant observation, with audio recording of the students’ discussions, their written work on the task and digital files of their work with technology. The results show that non-linear routes are associated with a greater mobilization of students’ knowledge on SLE concepts and with their development of modelling competencies. The results also highlight the need to improve the students’ competency of validating results, an important step that they did not take, and suggest the need to make technology relevant to the students’ work on modelling tasks.